Conjugate divergent margins: an introduction - Webster U. Mohriak; Al Danforth; Paul J. Post; David E. Brown; Gabor C. Tari; Michal Nemčok; Sudipta T. Sinha (2016)
The main objective of this book is to provide a global overview of divergent margins based on geological and geophysical interpretation of sedimentary basins along the South, Central and North Atlantic conjugate margins, from plate tectonics and crustal scales to a more detailed description of stratigraphical and structural elements that are responsible for petroleum plays. These themes are complemented by geodynamic concepts based on physical and numerical models, and by comparisons with present-day embryonic margins, which are succinctly discussed in some papers.